Democratic Republic of the Congo : Poverty Reduction Strategy Paper; Joint Staff Advisory Note. (IMF Staff Country Reports; Country Report, 2007)
This Joint Staff Advisory Note focuses on the Poverty Reduction Strategy Paper (PRSP) for the Democratic Republic of the Congo (DRC). The PRSP for Congo states that accelerated and sustainable economic growth will not be possible without a dynamic private sector engaged in job creation, development of industries, and competitive export sector. It emphasizes the role of growth as an important part of poverty reduction. In particular, it accords priority to rehabilitating road and energy infrastructure, including electrification of urban and rural areas.